PENERAPAN KAPITALISASI SEWA TERHADAP MANAJEMEN LABA - Sita Ayu Samsiah, (2023)
This research is a quantitative study that aims to find out how the application of capitalization leases, which are required due to the application of PSAK 73, affects earnings management. The sample in this study was all companies listed on the Indonesia Stock Exchange in the 2018-2021 period with the criteria for these companies disclosing an operating lease commitment and reporting minimum lease payments in the Notes to Financial Statements, and the final total sample companies were 37 companies with a total sample of 148. The data analysis technique in this study was to use multiple linear regression using panel data regression and also use a different test for the second hypothesis in this study, where the data processing program used was STATA v. software. Based on the results of the study, it was found that the capitalization of leases, as proxied by lease liabilities, has a significant negative effect on earnings management. Based on the results of the Wilcoxon tests, there is a difference between before and after the application of capitalization leases to earnings management.